DEVELOPMENT OF DISINTEGRATION CONTROL MATRIX TABLETS OF FEBUXOSTAT - Pralhad, Kanke (Asian Journal of Pharmaceutical Research and Development, 2018)
Disintegration control matrix tablet (DCMT) is a new approach for poorly water soluble drugs which successfully sustain the release up to 24hrs by controlling the disintegration rate of tablet. DCMT mainly forms the granules containing drug febuxostat and disintegrant sodium alginate which controls the release of febuxostat by controlling the rate of disintegration in wax coating plays an important role. The sustained release of drug is maintained by increasing the wax coating or decreasing the amount of disintegrant. The release of drug from tablet is uniform throughout till all the drug releases from tablet and it is justified by in-vitro dissolution studies. DCMT increases the solubility of drug and improves the bioavailability without disturbing gastrointestinal transit.